Human Resources Certification and Ship Safety Competency in Lake Toba - Maemunah, Siti; Aji, Adnan Bayu; Setiawan, Edhie Budi; Yuliantini, Yuliantini; Tatiana, Yana (Institut Transportasi dan Logistik Trisakti, 2025)
The aim of this research is to examine the effect of ship certification on ship safety mediated by human resource competency and ship stability. The research population was 135 crew members operating in Lake Toba port. The collection technique used non-probability sampling with purposive sampling. The sample in this study was 100 ship crew members. Data collection techniques included field research with questionnaires. The data analysis technique used Partial Least Squares of Structural Equation Modeling. The research results show that the certification process directly has a positive and significant effect on ship safety. The certification variable, mediated by ship stability, has a positive and significant effect on ship safety. However, when certification is mediated by human resources competency, it has no positive and insignificant effect. Further research is recommended related to standardization of port services to improve logistics’ performance.